2022
DOI: 10.1111/jsr.13628
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, insomnia and mental health

Abstract: Summary While sleep serves important regulatory functions for mental health, sleep disturbances, in particular insomnia, may favour a state of allostatic overload impairing brain neuroplasticity and stress immune pathways, hence contributing to mental disorders. In this framework, the aim of this work was to link current understanding about insomnia mechanisms with current knowledge about mental health dysregulatory mechanisms. The focus of the present work was on mood, anxiety, and psychotic disorders, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Several studies have also found more self-reported mental health problems in caregivers compared with non-caregivers [9,10] and caregivers appear to use more antidepressants than non-caregivers [14]. Insomnia and other mental health problems are often intertwined [15] and may follow from chronic stress [16,17], which has been reported in previous caregiver studies especially in high-intensity caregivers [9,18]. Caregivers included in the present study, i.e.…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have also found more self-reported mental health problems in caregivers compared with non-caregivers [9,10] and caregivers appear to use more antidepressants than non-caregivers [14]. Insomnia and other mental health problems are often intertwined [15] and may follow from chronic stress [16,17], which has been reported in previous caregiver studies especially in high-intensity caregivers [9,18]. Caregivers included in the present study, i.e.…”
Section: Discussionsupporting
confidence: 70%
“…The psychopathology of depression is complex and multifactorial with genetic and environmental drivers involved in the development. However, insomnia can precede the onset of symptoms and coexist as a comorbid condition, and is often a key feature of the clinical symptoms of depression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The current literature utilizes different approaches to describe the manifestations of insomnia such as the neurobiological, cognitive, behavioral, and emotional models. [19][20][21] Regardless of the model, there is a consensus that insomnia is the result of a dysregulation of brain centers containing the circadian rhythm and homeostatic processes that control sleep and wakefulness. 5 The ascending reticular activation system (ARAS) influences wakefulness while the ventrolateral preoptic region (VLPR) drives to sleep.…”
Section: Pathophysiologymentioning
confidence: 99%